MBIRA MUSIC OF RHODESIA, performed by Abraham Dumisani Maraire. 12-inch Stereo LP, with 12 page booklet — “Mbiras and Performance in Rhodesia” by Abraham Dumisani Maraire, introduction by Robert Kauffman. University of Washington Ethnic Music Series, UWP-1001, Robert Garfias, General Editor, University of Washington Press, Seattle and London, 1971 - Tracey, Andrew (International Library of African Music, 1971)
pages: 99-100
Keywords: Musical instruments; Mbira; Mbira music; African Music; Rhodesia; Zimbabwe; Mbira (Instrument); Musical Performance